2009
DOI: 10.1080/00036840701335553
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of micro-entrepreneurship: evidence from Argentina

Abstract: We analyse the nature of micro-entrepreneurship in Argentina. We focus on whether the sector resembles its counterpart in industrialized countries, characterized by the risk-taking nature of the entrepreneurial activity, or if it is the result of labour market distortions and disguised unemployment, as in the dual economy hypothesis. Our results suggest a segmentation of the micro-entrepreneur sector. Both young uneducated and middle aged highly educated salaried workers have the highest likelihood of becoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…Another interesting finding is that a prior experience of business failure increases risk aversion, and thus reduces the probability of becoming an entrepreneur. One study by Montes-Rojas and Siga (2009) shows that determinants of entrepreneurship vary by type: own-account workers and micro-entrepreneurs (eg. those who have some employees).…”
Section: Entrepreneurship Studiesmentioning
confidence: 99%
“…Another interesting finding is that a prior experience of business failure increases risk aversion, and thus reduces the probability of becoming an entrepreneur. One study by Montes-Rojas and Siga (2009) shows that determinants of entrepreneurship vary by type: own-account workers and micro-entrepreneurs (eg. those who have some employees).…”
Section: Entrepreneurship Studiesmentioning
confidence: 99%
“…Despite the relevance of the issue in emerging countries, the great majority of research relating the macroeconomic environment and entrepreneurship are directed to the reality of developed countries (Rojas & Siga, 2009;Mota et al, 2017). According to Rojas and Siga (2009), despite this, even in the context of countries in a more advanced economic stage, studies have shown that precarious economic conditions can lead individuals to endeavor as the only alternative for survival. Amorós et al (2016) have been developed for some time researches in the area of entrepreneurship in Latin American countries.…”
Section: Macroeconomic Environmentmentioning
confidence: 99%
“…Along the lines of proponents of the role of education in entrepreneurship levels, Rojas and Siga (2009) mention that previous research in developed countries has found evidence that formal education has a positive effect on the likelihood of an individual becoming an entrepreneur and that the ventures initiated by such individuals, due to their qualification and, consequently, level of perception have a greater chance of survival. They add that the educational level of the individual can be considered a predictor of the firm's success and mention that poor national education systems compel individuals to accumulate know-how and skills in the private sector to only then be able to embark on their own business.…”
Section: Educational Environmentmentioning
confidence: 99%
See 2 more Smart Citations